Visualisasi Feminisme dalam Film Jelita Sejuba: Mencintai Kesatria Negara melalui Karakter Syarifah - Agnes Septiana; Achmad Sjafi'i (Texture:Art and Culture Journal, 2022)
Jelita Sejuba movie: Loving the Knights of the Country is examined in terms of visualizing the feminism of the film’s main character, namely Syarifah. Although not a feminist movie, there are indications of feminism features  expressed  by  Syarifah’s  character  through  visual  language.  The  purpose  of  this  research  is  to describe  the  visualization  of  feminism  through  shots,  scenes,  gestures,  and  dialogues.  This  qualitative descriptive study applies a purposive sampling method by selecting the most appropriate scene as a sample. The analysis of feminism in this study is seen from the scenes which contain the visualization of feminism. The results of this study conclude that feminism can be presented through shots in movies that summarize scenes,  gestures,  and  dialogues.  The  visualization  of  feminism  presented  in  the  movie  shows  Syarifah’s attitude toward gaining the right to choose life according to her preferences.